The Effect of Revisit Intention on Brand Image in the Retail Industry: Brastagi Supermarket - Suriati Tirawani; Syaifuddin; Sofyan Matondang (MANAGER: Journal of Management and Administration Science, 2024)
More specifically, this research will investigate the factors that influence the perception of the Brastagi Supermarket brand. This research will focus on important factors that influence intention to revisit. How these components influence overall brand perception is the aim of this research. This research conducted a thorough case analysis with special emphasis on students studying at Prima Indonesia University to determine the preferences and behavior of this population. These findings will be presented by investigating these components in the context of the Brastagi supermarket. This research uses quantitative surveys and qualitative interviews. This method increases understanding of the complex relationship between intention to revisit and actions taken. It is hoped that the results of this research will contribute to academic research and provide advice to Brastagi Supermarket and other comparable retailers to improve their marketing strategies and encourage consumer participation. This research found that revisit intention has an effect on brand image in the retail industry.